2009
DOI: 10.1007/s11239-009-0357-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of renal function on argatroban therapy during percutaneous coronary intervention

Abstract: Argatroban, a hepatically metabolized direct thrombin inhibitor, is approved for anticoagulation in patients with or at risk of heparin-induced thrombocytopenia (HIT) undergoing percutaneous coronary intervention (PCI). We investigated the effect of renal function on argatroban therapy during PCI. From previous argatroban studies in PCI, we evaluated relationships between estimated creatinine clearance (CrCl) and activated clotting times (ACTs), dosage, and outcomes in 219 patients with or at risk of HIT (HIT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…75 Due to its metabolism by the liver, argatroban (initial or maintenance) dose adjustments for renal function are not needed during PCI. Hursting and Jang 97 reported in a retrospective analysis that ACT has no association to creatinine clearance with the use of argatroban during PCI for HIT patients.…”
Section: Percutaneous Coronary Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…75 Due to its metabolism by the liver, argatroban (initial or maintenance) dose adjustments for renal function are not needed during PCI. Hursting and Jang 97 reported in a retrospective analysis that ACT has no association to creatinine clearance with the use of argatroban during PCI for HIT patients.…”
Section: Percutaneous Coronary Interventionsmentioning
confidence: 99%
“…95,96 For patients with renal insufficiency, argatroban shows reliable dose-related anticoagulation activity in both non-PCI and PCI-treated patients. 90,97 Argatroban, as well as other DTIs, increases the INR, especially when it is bridged to warfarin therapy. When warfarin is given concomitantly with argatroban, the prothrombin time is excessively prolonged, and an INR of 4.0 can be regarded as equivalent to an INR 2.0 to 3.0 on warfarin only.…”
Section: Argatrobanmentioning
confidence: 99%
“…For HIT treatment, therapeutic levels of argatroban are achieved when the activated partial thromboplastin time is 1.5–3.0 times baseline 14. For PCI, therapeutic levels of argatroban are achieved when ACT is 300–450 s 14 16 17…”
Section: Case Seriesmentioning
confidence: 99%
“…In a retrospective Pharmacology of argatroban Drug Profile analysis of case records collected as part of prospective clinical studies of argatroban therapy in HIT patients, altered renal function did not significantly impact the aPTT response or the rates of thrombosis or bleeding associated with argatroban therapy [21]. A retrospective analysis of data obtained from prospective studies of argatroban therapy during percutaneous intervention indicated that renal dysfunction did not impact the initial activated clotting time (ACT) following bolus administration, the mean peri-procedural infusion dose or the need for multiple bolus doses [22]. However, there was the suggestion that the time required for the ACT to return to a level of 160 s or less was increased with renal dysfunction.…”
Section: Renal Impairmentmentioning
confidence: 99%